South Korea’s Entrepreneurial Model and its Global Impact - Manzura , Azamova (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2025)
South Korea has undergone a rapid economic transformation, evolving from an agrarian economy into a high-tech industrial powerhouse. This paper examines the South Korean entrepreneurial model, focusing on its phased development, government interventions, and global impact. The study also explores the adaptability of this model in Uzbekistan, analyzing key similarities and potential challenges. Furthermore, the research highlights the importance of integrating entrepreneurship into higher education to address student financial challenges and foster an innovation-driven economy. The paper employs a mixed-methods approach, incorporating both qualitative and quantitative analyses of South Korea’s startup ecosystem, innovation policies, and investment climate. The findings suggest that Uzbekistan can leverage South Korea’s strategies by implementing policy-driven entrepreneurial initiatives, enhancing startup infrastructure, and fostering technological entrepreneurship.